2001
DOI: 10.3201/eid0703.017312
|View full text |Cite
|
Sign up to set email alerts
|

Nipah Virus Infection in Bats (Order Chiroptera) in Peninsular Malaysia

Abstract: Nipah virus, family Paramyxoviridae, caused disease in pigs and humans in peninsular Malaysia in 1998-99. Because Nipah virus appears closely related to Hendra virus, wildlife surveillance focused primarily on pteropid bats (suborder Megachiroptera), a natural host of Hendra virus in Australia. We collected 324 bats from 14 species on peninsular Malaysia. Neutralizing antibodies to Nipah virus were demonstrated in five species, suggesting widespread infection in bat populations in peninsular Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(103 citation statements)
references
References 9 publications
0
102
1
Order By: Relevance
“…Yob et al [101] and Chua [12] have confirmed that fruit bats (popularly known as flying foxes) found in Malaysia, P. vampyrus and P. hypomelanus, are the natural reservoir hosts of NiV. The virus is assumed to have been introduced into the swine population from bat species of Pteropus.…”
Section: The Host Rangementioning
confidence: 95%
“…Yob et al [101] and Chua [12] have confirmed that fruit bats (popularly known as flying foxes) found in Malaysia, P. vampyrus and P. hypomelanus, are the natural reservoir hosts of NiV. The virus is assumed to have been introduced into the swine population from bat species of Pteropus.…”
Section: The Host Rangementioning
confidence: 95%
“…The grey-headed flying fox (Pteropus poliocephalus) and the black flying-fox (Pteropus alecto), both Pteropus spp. occurring in Malaysia were found seropositive for NiV [30]. Neutralizing antibodies, and the virus has been isolated from the small flying fox or variable flying fox (Pteropus hypomelanus) and the large flying fox (Pteropus vampyrus) [30][31][32].…”
Section: Species Susceptible To Nivmentioning
confidence: 99%
“…occurring in Malaysia were found seropositive for NiV [30]. Neutralizing antibodies, and the virus has been isolated from the small flying fox or variable flying fox (Pteropus hypomelanus) and the large flying fox (Pteropus vampyrus) [30][31][32]. NiV has been isolated from urine of Lyle's flying fox (Pteropus lylei) in Cambodia [33].…”
Section: Species Susceptible To Nivmentioning
confidence: 99%
See 2 more Smart Citations